2016
DOI: 10.1038/srep21986
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of traditional oriental medicine-derived monoamine oxidase B inhibitor on radioresistance of non-small cell lung cancer

Abstract: Increased survival of cancer cells mediated by high levels of ionizing radiation (IR) reduces the effectiveness of radiation therapy for non-small cell lung cancer (NSCLC). In the present study, danshensu which is a selected component of traditional oriental medicine (TOM) compound was found to reduce the radioresistance of NSCLC by inhibiting the nuclear factor-κB (NF-κB) pathway. Of the various TOM compounds reported to inhibit the IR activation of NF-κB, danshensu was chosen as a final candidate based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…24 Briefly, cells (1 × 10 4 in serum-free RPMI-1640 medium) subjected to the indicated treatments for 72 h were seeded into the upper chambers of a 24-well Transwell chamber (Corning, Corning, NY, USA) fitted with a 5 μm pore-size insert. The lower chamber was filled with RPMI-1640 medium containing 2% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…24 Briefly, cells (1 × 10 4 in serum-free RPMI-1640 medium) subjected to the indicated treatments for 72 h were seeded into the upper chambers of a 24-well Transwell chamber (Corning, Corning, NY, USA) fitted with a 5 μm pore-size insert. The lower chamber was filled with RPMI-1640 medium containing 2% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…The isolation of RNA, synthesis of cDNA and real-time RT-PCR were performed as previously described [28]. To isolate total RNA from A549 and NCI-H441 cells, Trizol® reagent (Thermo Fisher Scientific, Grand Island, NY) was utilized and RNA quality was assessed by agarose gel electrophoresis (visual absence of significant 18s and 28s rRNA degradation).…”
Section: Rna Extraction and Real-time Qrt-pcrmentioning
confidence: 99%
“…It has previously been established that Salvia miltiorrhiza Bunge is widely used in Traditional Chinese Medicine for the treatment of cardiovascular disease, and tanshinol extracted from S. miltiorrhiza Bunge has been identified to be the primary active component (10). Tanshinol has now been widely applied in various human diseases including cancer (11), chronic kidney disease (12) and heart disease (13). Previous data have demonstrated that tanshinol may decrease oxidative stress to avoid deleterious effects on tissue (14).…”
Section: Introductionmentioning
confidence: 99%